When objective group membership and subjective ethnic identification don't align: How identification shapes intergroup bias through self-enhancement and perceived threat. (June 2018) - Lee, I-Ching; Su, Jenny C.; Gries, Peter H.; Liu, Frank C. S.
When objective group membership and subjective ethnic identification don't align, which has a greater impact on how people feel towards the groups they affiliate with, and why? Deprived of many distinctiveness markers typically found in intergroup relations (e.g., physical features, obvious status differences), Taiwanese society provides a perfect natural context to explore the impact of objective group membership (Taiwanese nationality) versus subjective ethnic identification (Taiwanese or Chinese) on intergroup bias. Results from representative telephone ( N = 1, 060) and Internet ( N = 500) surveys demonstrated that even among participants with no visible distinctiveness markers or differences in social status, subjective ethnic identification contributed to intergroup bias in favor of Taiwanese over Chinese Mainlanders (main effect). Both self-enhancement (collective self-esteem as Taiwanese) and perceived threat from Chinese Mainlanders helped account for this finding (mediation effects). Implications for intergroup relations are discussed.